Computational studies of fuel and air mixing characteristics of a low pressure domestic gas appliance - Mustafa, A.; Nasri, N. S. (2003)

(untitled)
Computational fluid dynamics (CFD) simulation has been carried out to study the fuel and air mixing characteristics of a low pressure domestic gas appliance. Three types of liquefied petroleum gases (LPG), namely pure propane, pure butane and a mixture (by weight) of 30% propane and 70% butane, were simulated at a fuel pressure of 300 mm WG. The CFD results show that for the same fuel supply pressure and gas orifice size, the mass flow rate of LPG fuel discharged into a burner was proportionate to its specific gravity. However, as compared to butane and LPG mixture, the propane fuel discharge velocity was the highest due to its lowest specific gravity. This subsequently produced the most negative static pressure values at a burner mixing tube throat and hence allowing the largest amount of primary air to be induced into an appliance. The amount of primary air required to initiate combustion by propane, LPG mixture and butane fuels was predicted to be approximately 72%, 61% and 54% of stoichiometric requirement, respectively. These values are in good agreement with a typical range of primary air requirement for this type of atmospheric burner. The mixing rates of propane-air system were predicted to be much faster than that of LPG mixture-air and butane-air systems. However, for all three types of LPG fuel, the fuel and air mixing was found to be almost complete in the second mixing tube. In addition, the average mass fraction of fuel at a burner input was predicted to be almost identical to that of burner outlet, thus demonstrating a fully-premixed capability of this type of atmospheric gas appliance.